Analyzing the Interaction Between ABO Blood Types, Fingerprints, and Lip Prints among the Individuals of Lahore Region-A Research Article: Interaction Between ABO Blood Types, Fingerprints and Lip Prints - Iftikhar, Anwaar; Farooq, Rida; Zaroon, .; Rashid Daud, Jumana; Irfan, Muhammad; Naeem, Iqra; Akhtar, Mubeen; Mustafa, Usama; Ali, Muhammad; Maqsood, Quratulain (Pakistan Journal of Health Sciences, 2023)
Each person has a distinct lip printing and finger print, which are both utilized for personal identification and criminal investigations. Objective: To investigate the interaction between ABO blood group, lip prints and finger prints among both male and female participants. Methods: The study was conducted on 750 females and 550 males aged 18-50 from Lahore. Lip prints were classified using Tsuchihashi or Suzuki classification, while finger prints were classified using Kucken's or Michael's classification. Results were analyzed statistically using Microsoft Excel and SPSS version-21. Results: The pattern of loop was most common among the study group n = 1300 males (278 (50.55%), followed by Loop finger prints in 325 (43.30%) females. The most common blood type was AB+V 420(30%) among both groups. Both genders contain Type I lip pattern. The most common group of blood with fingerprint combination was AB+ve-Loop. AB+ve-Type I was the most common blood group versus lip print combination, with 104 individuals. Among the combination of lip prints or finger prints, Composite Type V had a smaller number of individuals. Both males and females scored 72. The composite type V-composite consists of A-ve, B-ve, AB-ve, or O-ve which showed the least common occurrence among the study group. Conclusions: Although blood typing, fingerprints, and lip prints each had unique characteristics. The correlation plays important role in identifying a certain person.